2017
DOI: 10.7146/torture.v27i1.26534
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of combined narrative exposure therapy and physiotherapy for comorbid PTSD and chronic pain in torture survivors

Abstract: Introduction: Torture is associated with adverse health consequences, with especially high rates of PTSD, depression and chronic pain. Despite increased awareness of the relationship between pain and posttraumatic symptoms, and the accompanying need for effective treatment strategies, few studies have examined an integrated treatment of comorbid PTSD and pain. Methods: In this study, using an A-B case series design with three and six month follow-up, six refugee torture survivors with comorbid PTSD, depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 21 publications
(23 reference statements)
0
35
0
Order By: Relevance
“…Physiotherapy, which integrates pain neuroscience education and other aspects of the biopsychosocial treatment of pain, has been used to treat persistent pain and functional impairments in the general population, those with mental health problems, and with survivors of torture (Amris & Williams, 2015). Additionally, the effectiveness of an interdisciplinary approach, combining psychotherapy and physiotherapy, for the treatment of pain and mental health problems has been explored (Dibaj et al, 2017;Kurklinsky et al, 2016;Mcgeary, Moore et al, 2011). However, globally, there are no studies examining an interdisciplinary treatment program for survivors of torture who are incarcerated.…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapy, which integrates pain neuroscience education and other aspects of the biopsychosocial treatment of pain, has been used to treat persistent pain and functional impairments in the general population, those with mental health problems, and with survivors of torture (Amris & Williams, 2015). Additionally, the effectiveness of an interdisciplinary approach, combining psychotherapy and physiotherapy, for the treatment of pain and mental health problems has been explored (Dibaj et al, 2017;Kurklinsky et al, 2016;Mcgeary, Moore et al, 2011). However, globally, there are no studies examining an interdisciplinary treatment program for survivors of torture who are incarcerated.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no current studies that have systematically examined symptom trajectories of refugees during treatment. Until now, only one case study depicted the course of symptoms in 6 refugees during a combination of NET and physiotherapy [48]. Otherwise, treatment studies with refugees have concentrated on a few assessment time points of symptoms only [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…However, exceptional experimental studies do exist, with substantial improvements found using the Common Elements Treatment Approach, compared to the less effective Cognitive Processing Therapy (Weiss et al, 2015). Quasiexperimental and outcome research on the rehabilitation of torture survivors provides further support for CBT (Halvorsen & Stenmark, 2010;Neuner et al, 2010) and NET (Dibaj, Overaas Halvorsen, Edward Ottesen Kennair, & Inge Stenmark, 2017;Hansen, Hansen-Nord, Smier, EngelkesHeby, & Modvig, 2017), culturally tailored health promotion intervention (Berkson, Tor, Mollica, Lavelle, & Cosenza, 2014) and educational groups (Phaneth, Panha, Sopheap, Harlacher, & Polatin, 2014). Furthermore, the literature reviewed indicates a strong prevalence of European and North American studies on the rehabilitation of torture survivors, with few outcome studies based in Africa.…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 97%